2002
DOI: 10.1002/1521-4095(20020404)14:7<489::aid-adma489>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoarrays Templated by Block Copolymers of Carbosilane Dendrimers and Polyisocyanopeptides

Abstract: Crystalline silver nanowires are formed inside micellar arrays of a template consisting of a (dendritic polysilane)/polyisocyanide block copolymer (see Figure). Silver ions, which coordinate to the peptide donor sites rather than the allylic end groups of the silane moiety, are reduced under the TEM electron beam to metallic silver (see also inside front cover).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…The utilization of high-energy irradiation such as plasma, electron beam or ion-beam removes the block copolymer template and generates nanoparticle arrays in a single step. 436,437 The fabrication of Au, Pd and Pt nanoparticle arrays was successfully demonstrated by utilizing PS-b-PVP micellar template. 438,439 Spatz et al showed the tunable interspacing of Co and Co 3 O 4 nanoparticle arrays by employing PS-b-PVP copolymer with different block lengths.…”
Section: Block Copolymers In Thin Filmsmentioning
confidence: 99%
“…The utilization of high-energy irradiation such as plasma, electron beam or ion-beam removes the block copolymer template and generates nanoparticle arrays in a single step. 436,437 The fabrication of Au, Pd and Pt nanoparticle arrays was successfully demonstrated by utilizing PS-b-PVP micellar template. 438,439 Spatz et al showed the tunable interspacing of Co and Co 3 O 4 nanoparticle arrays by employing PS-b-PVP copolymer with different block lengths.…”
Section: Block Copolymers In Thin Filmsmentioning
confidence: 99%
“…The synthesis of AgNPs generally involves the use of reducing agents [31][32][33][34][35][36] and organic stabilizers [19][20][21][22][23][24][25][26][27][28][29]. In this study, AgNO 3 was reduced in the presence of POE-functionalized SMA copolymers under exposure to visible light.…”
Section: Resultsmentioning
confidence: 99%
“…In general, the synthesis involves the reduction of silver ions (Ag + ) in the presence of organic stabilizers [16] and reducing agents [17]. Furthermore, silver nanostructures of various shapes [18], including spherical, triangular and fibrous morphologies have been reported by using polymer templates, including block copolymers [19][20][21], DNA [22,23], poly(acrylic acid) (PAA) [24], poly(vinyl pyrrolidone) (PVP) [25][26][27], poly(vinyl alcohol) (PVA) [28] and poly(styrene-alt-maleic anhydride) (SMA) [29]. Organic surfactants such as cetyltrimethylammonium bromide (CTAB) [30] may be present to form rod-shaped micelles which consequently direct the formation of the silver morphology.…”
Section: Introductionmentioning
confidence: 99%
“…One thorny problem in applied organometallic chemistry is setting up a general protocol for ligand synthesis and complex formation 1, 2. This is especially true in the case of carbene complexes,3, 4 where synthesizing ligand backbones from scratch can be a nightmare. This is a pity, since in many cases, and particularly with N ‐heterocyclic carbenes (NHCs), the resulting pre‐catalysts are air‐ and moisture‐stable 5–9.…”
Section: Introductionmentioning
confidence: 99%